A new topology for the trajectories of the meniscus during continuous steel casting - Risteski, Ice B. (Materiali in tehnologije, 2007)
The theoretical basis for a new computational method is given for the topology of the meniscus trajectories during continuous steel casting. The method is based on the solution of the meniscus equation in Â3. Here the topology is treated only in the sense of the categorization of trajectories in an orientation space. This suggests a new type of efficient self-adaptive scheme suitable for the solution of the shape of the meniscus. In the present work a new approach is used to overcome previously unknown pathological, non-physical predictions in various constitutive models derived using closure approximations. The generalized meniscus equation as well as its stability is solved. Here it is shown, for the first time, that the cyclic change of the shape of the meniscus depends on the coordinates, while up to now the cyclic change of the meniscus was presented only as a function of the time over the expression of the mould velocity.
Keywords: kontinuirno litje; trajektorije; meniskus